The impact of the dimensions of financial inclusion on the dimension of competitive advantage in Algerian banks -An applied study on a group of banking agencies in the state of Msila- - Alouane, samia; Bechichi, walid (Journal of Research in Finance and Accounting, 2025)
The objective of this study is to highlight the role that the dimension of financial inclusion play in achieving competitive advantage in Algerian banks by conducting exploratory research into the opinions of a sample of employees in banks in the state of Msila. To achieve the objectives of the study, the questionnaire consisting of three axes has been formulated. The first relates to personal data. The second is devoted to measuring the dimensions of financial inclusion. As for the third axis is dedicated to measuring the dimensions of competitive advantage, the study sample included one hundred and twenty (120) employees. The study reached several results and the most important there was a relation between the dimension of financial inclusion and the dimensions of competitive, the dimension of financial inclusion have a positive effect on the dimensions of competitive advantage, there is a direct relationship between the dimension of financial inclusion and competitive advantage, as every increase in the percentage of financial inclusion is followed by an increase in the percentage of competitive advantage , therefore financial inclusion has an impact on achieving competitive advantage from the point of view of banks workers.